Severity and prevalence of various types of mental ill-health in a general adult population: age and sex differences - Per Höglund; Camilla Hakelind; Steven Nordin (BMC Psychiatry, 2020)
Abstract Background Taking a broad approach, the aim of this study was to better understand severity and prevalence of various types of mental ill-health across age and sex groups in the general adult population. A first objective was to determine symptom severity of anxiety, depression, insomnia, burnout and somatization in combinations of different age groups and sex. A second objective was to determine prevalence of caseness of these types of mental ill-health in both absolute and relative terms in the combinations of age groups and sex. Methods Cross-sectional data based on validated questionnaire instruments were used from the Västerbotten Environmental Health Study in Sweden. In total, 3406 participants, aged 18 to 79 years, constituted a random sample stratified for age and sex. Results Severity and prevalence of anxiety, insomnia and burnout were high in women, in particular young women, and lower in older age groups. The prevalence rates for insomnia, burnout and somatization were particularly high based on the used cut-off scores. Men aged 30–49 years had the highest prevalence of mental ill-health compared to other age groups among men. Men and women aged 60–69 years had generally the lowest symptom severity and caseness. The prevalence of depression was similar in men and women in all age groups, whereas sex-related differences in extent in general were largest in the youngest age group, and gradually decreased with age. Conclusion The results suggest that focus in primary healthcare regarding mental ill-health should to be directed more towards insomnia, burnout and somatization, in particular in young women.